Photocatalytic reduction of Cr(VI) in a fully illuminated fluidized bed reactor - Pozzo, Roberto Luis (2011)
The potential of a fluidized bed reactor for the UV-A photocatalytic reduction of Cr(VI), a priority water pollutant, by utilizing a TiO2/quartz sand composite, was explored. The effects of oxalic acid (OA) as a sacrificial agent in the heterogeneous system was also investigated and compared with the homogeneous photoreduction by the same dicarboxylic acid under both, oxygenated or anoxic conditions of the reacting media. The performance of the "preconditioned" photocatalyst, either by pretreating it with the OA solution (at dark or under UV-A illumination) or by letting the catalyst to stand wet with the OA solution, during designated time intervals (one to five weeks) prior to its reuse, was assessed. Then, up to 95% reduction of Cr(VI) to Cr(III) was achieved in less than 100 minutes.